2005
DOI: 10.1179/174329405x49958
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption kinetics of benzyl triphenyl phosphonium chloride on mild steel in 1N sulphuric acid

Abstract: The inhibitive effect of benzyl triphenyl phosphonium chloride (BTPPC) on the corrosion of mild steel in aerated 1N sulphuric acid at different temperatures was investigated using galvanostatic polarisation, potentiostatic polarisation, infrared spectroscopy, scanning electron microscopy and quantum chemical studies. Corrosion potential, corrosion currents, cathodic and anodic Tafel slopes, heat of adsorption and effective activation energies were calculated in the presence and absence of the BTPPC. Inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…This indicates that DEA passivates the mild steel [25]. The passivation parameters may also be depending on the presence of the already adsorbed anions [26]. Temperature kinetics studies The adsorption kinetics and the effect of temperature on acid corrosion of metals in the presence and absence of DEA were studied.…”
Section: Potentiostatic Polarization Studiesmentioning
confidence: 99%
“…This indicates that DEA passivates the mild steel [25]. The passivation parameters may also be depending on the presence of the already adsorbed anions [26]. Temperature kinetics studies The adsorption kinetics and the effect of temperature on acid corrosion of metals in the presence and absence of DEA were studied.…”
Section: Potentiostatic Polarization Studiesmentioning
confidence: 99%
“…The inhibitory efficiency is closely related to the ability of the inhibitor to adsorb and the molecular properties of the different species of organic compounds [8][9][10]. Heterocyclic compounds, kind of effective inhibitors [11][12][13][14], have at least two factors within their structures, which is the reason of their effective inhibiting. The planarity (Π) and the lonely electron pairs in the heteroatoms are important features that determine the adsorption of these molecules on the metallic surface by transferring electrons from the organic compounds to the metal and forming a coordinate covalent bond during the chemical adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…It had been suggested that the most effective factors for the inhibiting effects are the electronegative atoms (such as, N, S, P, and O) [5,6], the unsaturated bonds (such as double bonds or triple bonds) [7,8], and the plane conjugated systems including all kinds of aromatic cycles, of which they can offer special active electrons or vacant orbital to donate or accept electrons. Heterocyclic compounds, kind of effective inhibitors [6][7][8][9], have at least two factors within their structures, which is the reason of their effective inhibiting. The planarity (_) and the lonely electron pairs in the heteroatoms are important features that determine the adsorption of these molecules on the metallic surface by transferring electrons from the organic compounds to the metal and forming a coordinate covalent bond during the chemical adsorption [6,7].…”
Section: Introductionmentioning
confidence: 99%